PENGEMBALIAN KERUGIAN KEUANGAN NEGARA SEBAGAI HAL YANG MERINGANKAN HUKUMAN DALAM TINDAK PIDANA KORUPSI - Budi Prakarsa Ketaren; Alvi Syahrin; M. Hamdan; Madiasa Ablisar (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2022)
The corruption is an axtradionary crime that damage and endagers the financial and economic of a state. If this nation did not aware the corruption as the root of problem, it is difficult for Indonesia to manage its self even for rise from the buried. The returning the loss of nation did not terminate the law prosecess on the corruption crime. But the returning of the loss of the state and followed by the elimination of the law process on corruption crime can be accepted as ultimate in corruption eradication. The problem in this thesis are : How the returning process of the state financial asset through the corruption crime justice as mentioned in the Act ? Did the returning the state financial will influence the punisment for criminal in the corruption crime justice ? What a returning of state financial in corruption crime justice in relationo to the objective of the punishment ? The asset recovery did not determined explicitly in Act No. 17/2003 concering to the State Financial and Act No. 20/2001 concering to theCorruption Crime Eradication even did not in Act No. 15/2002 that revised by Act No. 25/2003 concerning ti the money Laundry. The asset recovery is new nomenclatire and independent, separated from the term “State Financial”.this term indicate ecplicitly that asset of corruption is a property as the state asset. If the asset recovery had implemented in corruption crime justice, the judge is wise to provide the lower punishmen because the asset had be recovered.